2011
DOI: 10.1111/j.1750-3841.2011.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) Oil Bodies and Their Associated Phytochemicals

Abstract: Soybean oil bodies were isolated from 3 cultivars (Ustie, K98, and Elena) and the occurrence of 2 classes of phytochemicals (tocopherol isoforms and isoflavones) and strength of their association with isolated oil bodies was evaluated. Tocopherol is shown to be closely associated with soybean oil bodies; δ-tocopherol demonstrated a significantly greater association with oil bodies over other tocopherol isoforms. Isoflavones do not show a significant physical association with oil bodies, although there is some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Table shows that OBs contain all tocopherol isoforms, δ‐tocopherol is the major one, followed by β‐ and γ‐tocopherol, and α‐tocopherol is the minor one, in agreement with the results by Fisk and Gray (). It was found that total tocopherol was about 75 mg/100 g neutral lipid of OBs, which was not affected by pH.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Table shows that OBs contain all tocopherol isoforms, δ‐tocopherol is the major one, followed by β‐ and γ‐tocopherol, and α‐tocopherol is the minor one, in agreement with the results by Fisk and Gray (). It was found that total tocopherol was about 75 mg/100 g neutral lipid of OBs, which was not affected by pH.…”
Section: Resultssupporting
confidence: 90%
“…It was found that total tocopherol was about 75 mg/100 g neutral lipid of OBs, which was not affected by pH. It was reported that total tocopherol of pH 7.5 extracted OBs was 27 to 34 mg/100 g OBs for 3 varieties of soybean supplied by Soya U.K. Ltd. (Southampton, U.K.; Fisk and Gray ), which was obviously lower than the Chinese cultivar (Nannong 88–31) used in this study. The similar result was also found in one research that total tocopherol of extracted OBs obtained from another Chinese cultivar (Beixiang) was determined as about 73 mg/100 g OBs (Wu and others ).…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Similarly, the oil contained tocopherols, at a concentration of 36.29 mg/100 g of oil, almost all in the gamma form (97.75%), as it has ever been observed for other flaxseed varieties (Oomah et al, 1997;Schwartz et al, 2008). This content of gamma tocopherol is in the high range of those observed for other species (soybean oil: 27 mg/100 g (Grilo et al, 2014), soybean oil bodies: 12-23 mg/100 g (Fisk and Gray, 2011), rapeseed oil: 9 mg/100 g (Şeker et al, 2008) 39 mg/100 g (Schwartz et al, 2008), sunflower oil: 1.4 mg/100 g (Schwartz et al, 2008), 9 mg/100 mg (Grilo et al, 2014)). The presence of tocopherols, which work together with phospholipids which, as the neutral lipids, are mainly unsaturated (Herchi et al, 2012;Wanasundara et al, 1999), may improve the storage properties of freeze-dried oleosomes (Kamal-Eldin and Appelqvist, 1996;Doert et al, 2012).…”
Section: Release Of the Oil Bodies By Grinding The Seeds In Water Aftsupporting
confidence: 58%
“…Lipid will change the polarity of the product and act as a sink for hydrophobic volatile compounds [13,14], and additionally, lipid may be present as natural emulsions [15][16][17][18] or form emulsion droplets [19][20][21], oil layers or micelles [22,23] within the product during dispersion, which will impact the spatial distribution of lipophilic compounds and modify mixing behaviour [24,25]. Simple carbohydrates drive the partitioning of volatile compounds through salting-in and salting-out phenomena [26][27][28]; in an aqueous system, this is associated with the relative availability of water molecules in the continuous phase [22].…”
Section: Introductionmentioning
confidence: 99%